2003
DOI: 10.1016/s0925-4773(03)00046-7
|View full text |Cite
|
Sign up to set email alerts
|

Trl-GAGA directly interacts with lola like and both are part of the repressive complex of Polycomb group of genes

Abstract: Epigenetic inheritance to maintain the expression state of the genome is essential during development. In Drosophila, the cis regulatory elements, called the Polycomb Response Elements (PREs) function to mark the epigenetic cellular memory of the corresponding genomic region with the help of PcG and trxG proteins. While the PcG genes code for the repressor proteins, the trxG genes encode activator proteins. The observations that some proteins may function both as PcG and trxG member and that both these group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 47 publications
0
54
0
Order By: Relevance
“…As shown previously, the BTB domain of GAF can interact with BTB domains of Batman, 25,34 Pipsqueak, 26 Tramtrack, 23,33 and Mod(mdg4). 24 The question arises as to whether these BTB domains can interact with each other in different combinations.…”
Section: Testing Interactions Between Btb Domains In the Yeast Two-hymentioning
confidence: 52%
See 2 more Smart Citations
“…As shown previously, the BTB domain of GAF can interact with BTB domains of Batman, 25,34 Pipsqueak, 26 Tramtrack, 23,33 and Mod(mdg4). 24 The question arises as to whether these BTB domains can interact with each other in different combinations.…”
Section: Testing Interactions Between Btb Domains In the Yeast Two-hymentioning
confidence: 52%
“…[23][24][25][26] As controls, we used wellcharacterized BTB domains of human proteins Bcl6 and Miz1, which can form dimers 4 and tetramers, 10 respectively. We also examined the BTB domain of CP190, which has no significant homology to BTBs from the ttk group, and BTB from a vertebrate homolog of GAF identified recently.…”
Section: Btb Domains Of Gaf and Several Other Transcriptional Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In genetic assays conducted previously, no dominant interactions were detectable between Trl and Pc or ph for the eye phenotype (our unpublished results), whereas a genetic interaction in Hox gene regulation was found between Trl and a second member of the PcG / trxG, lolal (Faucheux et al, 2003;Mishra et al, 2003). Since interactions have not been systematically tested between Trl and other PcG / trxG genes for the eye phenotype, it cannot be excluded that other members of these groups control cell death in the eye.…”
Section: Cell Death and Cell Memory Genesmentioning
confidence: 68%
“…Two genes that share characteristics with both PcG and trxG genes, Trithorax-like (Farkas et al, 1994) (Trl) and lolal (also named batman, Faucheux et al, 2001;Faucheux et al, 2003;Mishra et al, 2003) were previously reported as displaying rough eyes in mutant escapers (Farkas et al, 1994;Faucheux et al, 2003) This phenotype could be reversed by introduction of trans- D,H,L). In Trl 13c escapers, the two horizontal sides (arrowheads in I,J,K) of each ommatidial hexagon appear shorter than the four oblique sides (arrows in I,J,K).…”
Section: Introductionmentioning
confidence: 99%